Microsteganography on all inorganic perovskite micro-platelets by direct laser writing. Issue 34 (17th August 2021) - Sheng, Yuhang; Liu, Cihui; Yu, Liyan; Yang, Yunyi; Hu, Fengrui; Sheng, Chong; Di, Yunsong; Dong, Lifeng; Gan, Zhixing
Abstract : A sophisticated direct laser writing technique is developed to pattern on CsPbBr3 perovskite micro-platelets for microsteganography. Abstract : Direct laser writing (DLW) is a mask-free and cost-efficient micro-fabrication technology, which has been explored to pattern structures on perovskites. However, there is still a lack of research on DLW methods for microsteganography. Herein, we developed a sophisticated DLW condition to pattern on CsPbBr3 perovskite micro-platelets (MPs). In addition to the reversible PL quenching caused by photo-induced ion migration, permanent nonradiative centers are also produced by the DLW treatment. Therefore, the patterned information is retained after long-term storage. Meanwhile, the mild DLW condition only results in a faint trace, which is almost invisible under a regular optical microscope. Thus, the patterned information is hidden unless applying an excitation source, which paves the way for applications in microsteganography and anti-counterfeiting. As a proof-of-concept, different patterns are drawn on the CsPbBr3 MPs by DLW, which are only observable under a fluorescence microscope.